Atmosphere and Materiality Respond to Rural Area Development. Case Study: Gereja Oikumene Sajau, North Borneo - Sofian, Tony (School of Design Universitas Pelita Harapan, 2023)
A wood-dominated architecture has a distinct meaning once humans recognize it. This study seeks to reveal the materiality of wood as one of the primary contemporary materials in the development of Indonesian architecture. The study was conducted in the Sajau Ecumenical Church, made primarily of wood and situated in a rural area of North Borneo. Understanding the concept of wood provides benefits beyond just using it as a building material. It also helps to comprehend how its existence is valued and expressed. This character stimulates human sensitivity. In addition, the wood material tactically creates a particular ambiance for those engaging with it.